Colloidal ZnO quantum dots based spectrum selective ultraviolet photodetectors - Kumar Y.; Kumar H.; Rawat G.; Kumar C.; Sharma A.; Pal B.N.; Jit S. (My University, 2025)
This letter reports (possibly for first time) the synthesis, fabrication, and characterization of a solution processed colloidal ZnO quantum dots (QDs) photoconductor-based spectrum selective ultraviolet (UV) photodetector on low-cost glass substrates without using any additional absorption tuning layer. The QD nature of colloidal ZnO was confirmed by transmission electron microscopy measurements in terms of average particle size (∼2.53nm) smaller than Bohr's radius (∼2.87 nm for ZnO). Furthermore, annealing at the ambient environment showed a shift in the bandgap from 3.231 to 3.136 eV of the ZnO QDs corresponding to the change in the annealing temperature from 450 °C and 600 °C. The responsivity characteristics showed a spectrum selective UV photoconductor nature with a full width half maximum of ∼49 nm and the maximum responsivity of ∼15.04 A/W at 2 V bias voltage and ∼360-nm operating wavelength. The response time and recovery time were measured as 7.2 and ∼18.5 s, respectively. The responsivity is believed to be the best among the reported ZnO QDs-based spectrum selective detectors. © 2017 IEEE.